Biomineralization From Molecular and Nano-structural Analyses to Environmental Science - Endo, Kazuyoshi; Kogure, Toshihiro; Nagasawa, Hiromichi (Springer Nature Singapore : Imprint: Springer, 2018)
This open access book is the proceedings of the 14th International Symposium on Biomineralization (BIOMIN XIV) held in 2017 at Tsukuba. Over the past 45 years, biomineralization research has unveiled details of the characteristics of the nano-structure of various biominerals; the formation mechanism of this nano-structure, including the initial stage of crystallization; and the function of organic matrices in biominerals, and this knowledge has been applied to dental, medical, pharmaceutical, materials, agricultural and environmental sciences and paleontology. As such, biomineralization is an important interdisciplinary research area, and further advances are expected in both fundamental and applied research. .